Kegiatan knowledge sharing dalam meningkatkan literasi kesehatan ibu menyusui di AyahASI Indonesia - Rully Khairul Anwar; Andy Mananohas; Tine Silvana Rachmawati (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. This research aims to identify and understand the sharing of knowledge in improving health literacy of breastfeeding mothers at AyahASI Indonesia. Data Collection Methods. This research used a qualitative method with case study approach. Data collection techniques were carried out through observations, interviews and literature studies. Data Analysis. Data analysis technique was conducted using the knowledge conversion theory. The stages of data analysis included description, reduction, and selection. Subject of this research is one founder and two followers. Results and Discussion. Findings of this study explain that the knowledge sharing process at AyahASI Indonesia includes socialization, externalization, combination, and internalization. Results involve managers and followers in sharing knowledge either through direct communication such as gatherings or indirect communication such as using social media. Several obstacles faced were the use of language, scope of implementation, unethical milk marketing formulas, funds, and human resources. Conclusion. Knowledge sharing activities at AyahASI Indonesia aims to improve health literacy of breastfeeding mothers in order to be successful in providing breast milk to children. Suggestions can be started by forming a more reliable management system, expanding members to areas that have not been reached, selective in choosing words and collaborating with more health workers.